Learning Obstacle Student in Factoring Quadratic Form - B A Saputro; D Suryadi; R Rosjanuardi; B G Kartasasmita (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The purpose of this study is to understand students' mistakes in using the cross methodto factorize the squared form. Eight quadratic form factoring is given to students to obtain studentlearning barrier data. The data were analysed in accordance with the phase of the cross method,followed by the interview to validate the alleged category of learning obstacle types that occurredin each student. The results of this study indicate that the obstacle learning that many studentsexperience using the cross method is didactical obstacle which is one example of the mistakethat student’s fact squared form by not involving variable x.